2018
DOI: 10.1002/aocs.12176
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Oil Types and Storage Conditions on Milk Fat Quality of Strained Yogurt Immersed in Oil

Abstract: To maintain strained yogurt freshness, it was shaped into balls (3-3.5 cm diameter), completely immersed in oil, and stored at refrigerated or ambient temperature for 6 months. The impacts of immersing strained yogurt in oil on the topped oil and product's final quality of lipids including fat oxidation, lipolysis, cholesterol oxidation, and conjugated linoleic fatty-acid content (CLNA) (i.e., as freshness indicators), during storage under various storage conditions, were evaluated. Peroxide value (PV), 7-keto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The content of FFA (expressed as % of oleic acid), used to monitor the hydrolytic degradation of lipids, increased in EVOOs stored with the addition of cheese, especially after two months ( Table 1 ). The expansion of FFA was also reported by Al-Ismail et al [ 4 ] for olive oil samples stored with strained yogurt balls for two months in dark at room temperature (23.3 °C). Generally, the esters of long-chain FFAs (present in EVOO) do not hydrolyze easily [ 33 ].…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…The content of FFA (expressed as % of oleic acid), used to monitor the hydrolytic degradation of lipids, increased in EVOOs stored with the addition of cheese, especially after two months ( Table 1 ). The expansion of FFA was also reported by Al-Ismail et al [ 4 ] for olive oil samples stored with strained yogurt balls for two months in dark at room temperature (23.3 °C). Generally, the esters of long-chain FFAs (present in EVOO) do not hydrolyze easily [ 33 ].…”
Section: Resultssupporting
confidence: 78%
“…The obtained results ( Table 1 ) have shown that the presence of any type of cheese caused no major increases in the PV of topping oils, considering that the levels remained slightly above those of control oils. The same occurrence was noted in EVOOs used as topping oil for strained yogurt balls in which PV was unchanged, even lower, compared to fresh EVOO during two-month storage in the dark and at 4 °C [ 4 ].…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations